Helminth parasite communities of allopatric populations of the frog Leptodactylus podicipinus from Pantanal, Brazil - Campiao, K. M.; Silva, R. J. da [UNESP]; Ferreira, V. L. (Cambridge University Press, 2014)
Several factors may influence the structure of parasite communities in amphibian hosts. In this study, we describe the helminth parasites of three allopatric populations of the frog Leptodactylus podicipinus and test whether host size and sex were determinants of the structure and composition of the helminth communities. One hundred and twenty-three anurans were collected from three different study sites within the Pantanal wetlands and surveyed for helminth parasites. We found 14 helminth taxa: 7 species of nematodes, 4 species of trematodes, 1 species of cestodes, 1 species of acanthocephalan and one unidentified cyst. Host sex and size did not cause significant differences in helminth abundance or richness. The structure of helminth communities from the three study sites varied in terms of species composition, abundance and diversity. Six out of 14 helminth taxa were found in the three localities. Among those, the nematodes Cosmocerca podicipinus and Rhabdias sp., the trematode Catadiscus propinquus and the helminth cyst showed significant differences in mean abundances. We suggest that such differences found among the three component communities are driven by biotic and abiotic factors operating locally. Moreover, these differences stress the importance of local conditions, such as hydrologic characteristics and landscape composition, on helminth community structure.